C-Met as a Key Factor Responsible for Sustaining Undifferentiated Phenotype and Therapy Resistance in Renal Carcinomas - Marona, Paulina (Cells, 2019)
C-Met tyrosine kinase receptor plays an important role under normal and pathological conditions. In tumor cells’ overexpression or incorrect activation of c-Met, this leads to stimulation of proliferation, survival and increase of motile activity. This receptor is also described as a marker of cancer initiating cells. The latest research shows that the c-Met receptor has an influence on the development of resistance to targeted cancer treatment. High c-Met expression and activation in renal cell carcinomas is associated with the progression of the disease and poor survival of patients. C-Met receptor has become a therapeutic target in kidney cancer. However, the therapies used so far using c-Met tyrosine kinase inhibitors demonstrate resistance to treatment. On the other hand, the c-Met pathway may act as an alternative target pathway in tumors that are resistant to other therapies. Combination treatment together with c-Met inhibitor reduces tumor growth, vascularization and pro-metastatic behavior and results in suppressed mesenchymal phenotype and vascular endothelial growth factor (VEGF) secretion. Recently, it has been shown that the acquirement of mesenchymal phenotype or lack of cell differentiation might be related to the presence of the c-Met receptor and is consequently responsible for therapy resistance. This review presents the results from recent studies identifying c-Met as an important factor in renal carcinomas being responsible for tumor growth, progression and metastasis, indicating the role of c-Met in resistance to antitumor therapy and demonstrating the pivotal role of c-Met in supporting mesenchymal cell phenotype.